Escalada tarifária do café e o novo acordo comercial Mercosul-União Europeia - Silva, Bruno Santos Pelegrini da (Universidade Federal de São Carlos, 2022)
The main objective of this work was to identify the existence of tariff escalation for the productive coffee chain for the year 2019. We used two methods to find the effective protection: Nominal Tariff and The Effective Rate of Protection. Additionally, the analysis developed relates these results with the new tariff offers proposed by the European Union in the new agrément to assess a possible reduction or elimination of the tariff escalation. The results show evidence of tariff escalation for the coffee production chain and its elimination within a maximum period of 7 years after the Agreement comes into force. Therefore, it was concluded that the hypothesis of tariff escalation is valid and that this fact harms the national agribusiness's expansion. In addition to eliminating the tariff escalation for the coffe chain, the new Mercosur-European Union Trade Agreement can also bring benefits such as an increase in GDP and agribusiness development. However, Mercosur member countries will need to undergo regulatory reforms to comply with the current regulation in Europe.
Coffee tariff escalation and the Mercosur-EU trade agreement
Keywords: Escalada Tarifária; Cadeia Produtiva do Café; Mercosul; União Europeia; Tariff Escalation; Coffee Production Chain; Mercosur; European Union; CIENCIAS SOCIAIS APLICADAS::ECONOMIA